Sistem Pendukung Keputusan Seleksi Pemilihan Ajang Service Ambassador Medan Menerapkan Metode VIKOR (Studi Kasus: Pt. Midi Utama Indonesia Tbk) - Cici Mulya Sari; Surya Darma Nasution; Ronda Deli Sianturi (Jurnal Sistem Komputer dan Informatika (JSON), 2020)
The selection of the Service Ambassador event is a consistent manifestation of PT. Midi Utama Indonesia Tbk, so that the best service can be accepted by the community. Service Ambassador is one of the selection of employees precisely with the best cashier position. Improving customer service skills must be a priority every day for every business that wants to excel in today's competitive market. Moreover, every interaction with the customer, provides an opportunity for customers to spread the best service to other potential customers. Through the selection of the Medan Service Ambassador, PT Midi Utama Indonesia Tbk moved more aggressively to improve services. The method used in this decision support system is the VIKOR (Vise criterijumsko Kompromisno Rangiranje) method. This method ranks alternatives and determines the ideal compromise solution, so that this system can later benefit PT. Midi Utama Indonesia Tbk to get the title in determining the best Medan Ambassador service employees to be referred to the national level. From the selection results of the Service Ambassador event, PT. Midi Utama Indonesia Tbk, hopes that the best service is truly acceptable to the community and can increase the level of sales which is greatly improved which can be beneficial for PT. Midi Utama Indonesia Tbk